Formação inicial de professores de Ciências Biológicas e o uso de recursos tecnológicos digitais no contexto de ensino remoto emergencial - Tomazini Neto, Bruna Cristina (2023)
The technological society in which we have been living has made available to us several possibilities to access information and communication. This context has affected all public and private sectors, including education, which had to “reinvent” itself to meet the demands of this new society. However, it is not enough to guarantee students’ creativity, autonomy and learning just because digital technological resources were inserted in the classroom. Teacher must think about, debate and analyze the applied digital technological resources and based on them, look for spaces that can fullfill students' demands. During the pandemic context, teachers’ training courses were integrated with several digital technological resources. Thus, we aimed at understanding if and how emergency remote teaching may have mobilized new understandings and (re)significations regarding technologies for the initial training of Science teachers, based on a research problem associated to some activities that were developed in the Curricular Supervised Internship. The study assumes a qualitative character of field research, as it is exploratory research, from a non participant observation. It involved students who were enrolled in the Mandatory Internship in Science II discipline, from the Biological Sciences Degree Course at a Federal University. As research instruments, the proposal involved data in files produced by the participants – questionnaire, lesson plans, reflective sheets, and final works, in addition to video recording of the followed classes. The obtained data set was analyzed using the Discursive Textual Analysis (DTA). According to this analysis, two categories emerged: 1. A glimpse into technologies: from understandings to teaching practices in Science Teaching - when we discussed the students’ understandings about the technology concept and how these subjects applied digital technological resources in the teaching practice of Supervised Internship; 2. Revealing the background: interactions mobilized by the application of digital technological resources, in which we thought about technical and pedagogical interactions that occur along the teaching and learning processes, when using digital technological resources. Finally, we understood that it is essential to improve in teachers’ training actions, as well as it is important to go beyond the simple instrumentalization when using technological resources. It is also necessary to think about training for the didactic application of digital technological resources. Therefore, creating spaces strategically designed for the teaching staff to try, test, discuss and exchange experiences regarding didactic possibilities helped the teacher to think about alternatives to take part of their practices with digital technological resources applications.